PENGARUH JUMLAH BUKU TERHADAP PERTUMBUHAN SETEK CABANG BAMBU BETUNG, ANDONG, TEMEN, AMPEL HIJAU, AMPEL KUNING, ORI, TALI DAN HITAM PADA KULTUR AIR - Sandra Arifin Aziz; , Adiwirman (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1997)
One and two nodes (if branch cuttings were use as vegetative propagation material in water culture, which is the dipping of all the nodes of branch cuttings in the water. Experiment was carried out on eight bamboo species: Dendrocalamus asper, Gigantochloa pseudoarundinacea, G. atter, Bambusa vulgaris green and yellow, B. bam boos, G. apus and G. atroviolacea, with one and two nodes branch cuttings. Only three species had been propagated successfully by this method, which were green and yellow B. vulgaris and G. apus. No significant growth difference was observed between one and two nodes branch cuttings. Growth percentage of green B. vulgaris on experiment 1, 2 and 3, yellow B. vulgaris and G. apus were 40, 56.25, 55, 30 and 9.38% respectively.